Results of Screening for Retinopathy of Prematurity: How the Ideal Screening Program Should Be? - Ebru Esen; Elif Erdem; Kemal Yar (Türk Oftalmoloji Dergisi)
Objectives: To determine the rate of infants with retinopathy of prematurity (ROP) requiring treatment, to investigate the relation of this rate with birth age and birth weight, and to discuss the screening criteria eligible for our country. Materials and Methods: Medical records of premature infants examined for ROP with birth weight ≤2000 gram (g) and/or gestational age ≤34 weeks were evaluated. Patients were grouped according to their birth weights as ≤1000 g, 1001-1500 g, >1500 g, and according to gestational age as ≤27 weeks, 28-31 weeks, ≥32 weeks. The rate of patients with treatment-requiring ROP was evaluated in these groups. The birth weights and gestational ages of these patients were analyzed. Results: Treatment requiring ROP stages were detected in 100 (8%) of 1250 infants. The mean gestational age and birth weight of these patients was 28.3±2.3 (24-34) weeks and 1152.2±396 (520-2120) g respectively, and both were found lower than those of nontreated infants (p<0.001). Regarding the birth weight, 45 (22.3%) of 202 infants ≤1000 g, 39 (%8) of 488 infants between 1001- 1500 g, 16 (%2.9) of 560 infants >1500 g required treatment. According to the gestational age, 33 (19.4%) of 170 infants ≤27 weeks, 59 (10.3%) of 572 infants between 28-31 weeks, 8 (1.6%) of 508 infants ≥32 weeks required treatment. Conclusion: The best way to avoid the vision loss due to ROP is to establish a regular screening program including every infant that may require treatment. So we recommend that screening criteria for our country should be wider than applied in developed countries, and babies having gestational age ≤34 weeks and/or birth weight ≤2000 g should be screened for ROP. (Turk J Ophthalmol 2014; 44: 42-6)